Assessment of functional outcomes in patients with head and neck cancer according to the International Classification of Functioning, Disability and Health Core Sets from the perspective of the multi‐professional team: Results of 4 Delphi surveys. Issue 7 (18th September 2013) - Kirschneck, Michaela; Sabariego, Carla; Singer, Susanne; Tschiesner, Uta
ABSTRACT Background The International Classification of Functioning, Disability and Health Core Set for Head and Neck Cancer (ICF‐HNC) covers the typical spectrum of problems in functioning in head and neck cancer. This study is part of a multistep process to develop practical guidelines in Germany. The purpose of this study was to identify instruments for the assessment of functioning using the ICF‐HNC as reference. Methods Four Delphi surveys with physicians, physiotherapists, psychologists, and social workers were performed to identify which aspects of the ICF‐HNC are being treated and which assessment tools are recommended for the assessment of functioning. Results Ninety‐seven percent categories of the ICF‐HNC were treated by healthcare professionals participating in the current study. Altogether, 33 assessment tools were recommended for therapy monitoring, food intake, pain, further organic problems/laboratory tests, and psychosocial areas. Conclusion Although the ICF‐HNC is being currently implemented by the head and neck cancer experts, several areas are not covered regularly. Additionally, validated tools were rarely recommended. © 2013 Wiley Periodicals, Inc. Head Neck 36: 954–968, 2014